THE EFFECT OF ELECTRONIC HUMAN RESOURCE MANAGEMENT PRACTICES IN ENHANCING THE ROLES OF KNOWLEDGE WORKERS: AN APPLIED STUDY AT THE HEADQUARTERS OF THE IRAQI MINISTRY OF HEALTH AND ENVIRONMENT - Zakaria Hamid Khalil Hassan Zour, Samah Mouyad Mahmoud Al-Moula, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The researcher aims, through the current study, to identify the impact of electronic human resource management practices in the Iraqi Ministry of Health and Environment through the main study axes (e-recruitment, electronic training and development, electronic performance evaluation, and electronic compensation), and their level of contribution to enhancing the roles of knowledge Workers from During the main axes represented by (observer, participant, organizer, learner) and the problem of the study, which the researcher reached through the initial exploratory study that he conducted for the study community, the Iraqi Ministry of Health and Environment applies some electronic human resource management practices, but not in an integrated manner. In addition, no evaluation process was conducted on the level of application of these practices and the challenges they face, and the extent to which these practices reflect on the roles of knowledge workers and their enhancement in the researched ministry. Where an intentional random sample was chosen consisting of (224) managers and directors representing the study community, and To achieve the hypothesis test, the researcher used the descriptive and analytical method, and the questionnaire was relied on as a main tool for the study in collecting data, and to achieve this, a main hypothesis was formulated from which (4) sub-hypotheses were formed. And tested using SPSS program and a set of statistical methods, including (simple linear regression). Through the study, the researcher reached a set of results, perhaps the most prominent of which is the Iraqi Ministry of Health and Environment applying some electronic human resource management practices, which are both (electronic employment and electronic compensation) and this was confirmed in the results of the practical side.